2011
DOI: 10.1039/c0sc00330a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed coupling of functionalized primary and secondary amines with aryl and heteroaryl halides: two ligands suffice in most cases

Abstract: We report our studies on the use of two catalyst systems, based on the ligands BrettPhos (1) and RuPhos (2), which provide the widest scope for Pd-catalyzed C–N cross-coupling reactions to date. Often low catalyst loadings and short reaction times can be used with functionalized aryl and heteroaryl coupling partners. The reactions are highly robust and can be set up and performed without the use of a glovebox. These catalysts should find wide application in the synthesis of complex molecules including pharmace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
212
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(216 citation statements)
references
References 83 publications
2
212
0
2
Order By: Relevance
“…The O-alkylated product of phenol (3) underwent the Smiles rearrangement by the nucleophilic attack of the nitrogen atom on the carbon of the benzene ring attached to the oxygen atom, which led to the formation of a new C-N bond to give spiro-intermediate (6). With the bond breaking of C-O bond, then came the intermediate (7). Under alkaline conditions (with Cs 2 CO 3 or NaH) in DMF, intermediate (8) was decarboxylated to afford the N-azaaryl anilines (5).…”
Section: Resultsmentioning
confidence: 99%
“…The O-alkylated product of phenol (3) underwent the Smiles rearrangement by the nucleophilic attack of the nitrogen atom on the carbon of the benzene ring attached to the oxygen atom, which led to the formation of a new C-N bond to give spiro-intermediate (6). With the bond breaking of C-O bond, then came the intermediate (7). Under alkaline conditions (with Cs 2 CO 3 or NaH) in DMF, intermediate (8) was decarboxylated to afford the N-azaaryl anilines (5).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, we have recently extended this cycloaddition methodology to the Diels-Alder reaction between 1-alkynylphosphine oxides and anthracene to afford the electron-rich biaryl-like KITPHOS class of monophosphines 50-52 -architectural analogs of Buchwald's biaryl-like monophosphines [53][54][55][56] . Preliminary studies have shown that these monophosphines are highly efficient ligands that either rival or outperform their biaryl-based counterparts in palladium-catalyzed Suzuki-Miyaura and Buchwald-Hartwig cross-couplings 50,51 , a host of gold(I)-catalyzed intramolecular cycloisomerizations [57][58][59] , as well as in the ruthenium-catalyzed direct ortho arylation of 2-phenylpyridine and N-phenylpyrazole with aryl chlorides 60 .…”
Section: Simon Doherty and Catherine H Smythmentioning
confidence: 98%
“…Recently, Buchwald used diimine as ligand for effective copper-mediated crosscoupling reactions under mild conditions [15]. Very recently, Buchwald et al and others have reported a copper-based protocol for the formation of N-aryl bonds [16][17][18]. Immobilization of the soluble catalysts onto an insoluble matrix using a simplified protocol will allow easy separation and recyclability of the catalyst with minimal amount of product.…”
Section: Introductionmentioning
confidence: 98%